Penguatan Muatan Lokal Untuk Pengembangan Ekowisata di Desa Lodtunduh, Kecamatan Ubud, Gianyar - Anak Agung Inten Mayuni; Ida Bagus Astika Pidada (Universitas Warmadewa, 2021)
Lodtunduh is one of the villages located in the sub-district of Ubud, Gianyar district and is a buffer for world tourism destinations with an emphasis on ecotourism. Lodtunduh village has the potential of various local contents (local constant) which can be optimized for its function for the development of ecotourism. The amount of potential local content that can be developed in supporting tourism has not been followed by optimal results. Therefore, in this service it is necessary to focus on understanding: 1) what local content can be developed for ecotourism development in Lodtunduh village; 2) How to develop local content so that it is useful or functional for ecotourism development, and 3) What are the implications of strengthening local content for the welfare of the Lodtunduh village community. The theory used to analyze is the functional theory of A-G-I-L Talcot Parsons that every action will always be related to Adaptation, Goal, Integration, Latency. Because this community service is carried out in conjunction with the 2021 Warmadesa University Real Work Lecture, direct observation (observation) and interviews (interviews) are the main data collection techniques as well as using library studies. From the results of this Community Service, it was found that Lodtunduh village has the potential of local content including, classic to modern paintings, kite crafts, masks, kris, making silungan tape, rice terraces, beautiful cliffs, development of the Dalem Alas Harum ecotourism area. Haretige. It's just that all these potentials have not been developed optimally, not only due to the Covid-19 pandemic situation, but also because they are done conventionally. Therefore, education about more intensive online promotion is needed, so that the local potential of content owned by Lodtunduh village is widely and massively distributed and efficient. wawancara (interviewe) menjadi Teknik pengumpulan data yang utama disamping juga menggunakan studi kepustakaan. Dari hasil Pengabdian Masyarakat ini ditemukan bahwa desa Lodtunduh memiliki potensi muatan lokal (local contant) diantaranya, lukisan klasik hingga modern, kerajinan layang-layang, topeng, keris, pembuatan tape silungan, terasering persawahan, tebing yang indah, pengembangan kawasan ekowisata Dalem Alas Harum Haretige. Hanya saja semua potensi itu belum dikembangan secara optimal, tidak saja disebabkan oleh situasi pamdemi covid-19, tetapi juga karena dikerjakan secara konvensional. Oleh karena itu, diperlukan edukasi tentang promosi online yang lebih intensif, agar potensi lokal konten yang dimiliki oleh desa Lodtunduh tersebar secara luas dan masif serta berdaya guna.